Isolation of triterpenoid saponins from Medicago sativa L. with neuroprotective activities. Issue 4 (15th February 2020) - Li, Danqi; Liu, Da; Lv, Mengchao; Gao, Pinyi; Liu, Xuegui
Graphical abstract: Abstract: Three new pentacyclic triterpenoid saponins (1 –3 ), together with medicagenic acid (4 ) were isolated and purified from 70% EtOH extract of Medicago sativa L. by different column chromatographic and semi-preparative HPLC. Their structures were established by direct interpretation of their spectral data, mainly HR-ESI-MS, 1D-NMR, 2D-NMR, and chemical methods, as well as comparison with literature data. Additionally, all isolates were evaluated for their neuroprotective activities against H2 O2 -induced damage in human neuroblastoma SHSY5Y cells. As a results, compounds 1 and 2 (67.14% and 73.05%) exhibited potent neuroprotective activities. These findings provide new insights into developing better treatment of neurodegenerative diseases for M . sativa in the future.